COMPARING LEXICAL DENSITY IN TEACHER TALKS: ELEMENTARY SCHOOL AND HIGHER EDUCATION LEVEL - Ismail, Nyak Mutia; Yoestara, Marisa; Jamilah, Sitti (LLT Journal: A Journal on Language and Language Teaching, 2023)
Teacher talk must be specific, clear, concise, and comprehensible for students as the target interlocutors. This study aimed to characterize lexical density in teacher talks of elementary school teachers and university lecturers during teaching. A qualitative descriptive technique was used involving lexico-grammar analysis from an SFL perspective. The subjects of this study were three elementary school teachers (6th-grade teachers) and three university lecturers (English lecturers) who were voluntarily recorded during their teaching time; once for each. Hence, the object of this study is the transcriptions of teacher talks from these six research subjects which were then analyzed using documentation techniques of data analysis namely selection, categorization, classification, identification, and verification. The results show that the lexical density used in elementary school teacher talk is 42.65% (low) and that one employed at the university level is 36.76% (low). Unexpectedly, the rate for elementary school is somewhat higher than that for the university level. This case appears to have an intervening aspect because the elementary school is an international school. It is learned that an educational institution—regardless of its level—with a distinct learning target would certainly influence the lexical density employed in the teachers’ spoken discourse during classes.